1990
DOI: 10.1007/bf01868671
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cl− transport in vacuolar membrane vesicles using a Cl−-sensitive fluorescent probe: Reaction kinetic models for voltageand concentration-dependence of Cl− flux

Abstract: The effects of Cl- concentration and membrane potential (delta psi) on Cl- influx in isolated vesicles of vacuolar membrane (tonoplast) from red beet (Beta vulgaris L.) storage tissue have been characterized using the Cl(-)-sensitive fluorescent probe, 6-methoxy-1-(3-sulfonatopropyl)quinolinium (SPQ). The initial rate of Cl- transport into the vesicles was enhanced both by the imposition of a positive delta psi and by increases in extravesicular Cl- concentration. The kinetic mechanism underlying these respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This permeability sequence is characteristic of several anion channels derived from vacuolar membranes (cf. Hedrich, Flugge & Fernandez, 1986;Pope & Leigh, 1988;Pope et al, 1990;. Most striking, however, is the voltage dependence of the channel.…”
Section: Gating Of the K ~ Inward Rectifier Is Sensitive To H +mentioning
confidence: 91%
“…This permeability sequence is characteristic of several anion channels derived from vacuolar membranes (cf. Hedrich, Flugge & Fernandez, 1986;Pope & Leigh, 1988;Pope et al, 1990;. Most striking, however, is the voltage dependence of the channel.…”
Section: Gating Of the K ~ Inward Rectifier Is Sensitive To H +mentioning
confidence: 91%
“…These experiments demonstrated that CI-could be electrically driven into the vesicle interior, and also suggested that C1-may enter via a saturable uniport whether driven by A 0 or by a C1-concentration gradient alone ( Fig. 4; see also Pope et al 1990). By imposing a range of K+-diffusion potentials, at a fixed external C1-concentration, flux voltage (F-V) curves could be generated (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These are directly analgous to current-voltage (I-V) curves which are a major tool in electrophysiological studies. In a separate paper, we have used such data to investigate the kinetic mechanisms underlying the responses of C1-flux to changes in both A 0 and C1-concentration (Pope et al 1990). At a C1-concentration of 10 mol.m -3, influx was most sensitive to AO at values between +25 mV and + 55 mV (Fig.…”
Section: Discussionmentioning
confidence: 99%